Validity of an FFQ assessing the vitamin D intake of young Serbian women living in a region without food fortification: the method of triads model. Issue 3 (11th May 2015) - Djekic-Ivankovic, Marija; Weiler, Hope A; Nikolic, Marina; Kadvan, Agnes; Gurinovic, Mirjana; Mandic, Ljuba M; Glibetic, Maria
Abstract: Objective: The objective of the present study was to examine the external validity of an FFQ designed to estimate dietary vitamin D intake compared with a plasma biomarker and three repeated 24 h dietary recalls in women of reproductive age in Serbia, where there is no exposure to food fortified with vitamin D. The method of triads was applied. Design: In a cross-sectional study, 422 women completed the Women and Reproductive Health FFQ (WRH-FFQ) during the winter months. From a representative subgroup ( n 44), three 24 h dietary recalls and anthropometric parameters were collected as well as a fasting blood sample for vitamin D biomarker analyses. Correlation coefficients were calculated between each of the dietary methods. Validity coefficients, as a correlation between the measured and estimated 'true' exposure, were calculated using the method of triads. Bland–Altman plots were also constructed. Setting: Three major universities in Serbia. Subjects: Healthy young women ( n 422) aged 18–35 years. Results: The WRH-FFQ estimate of vitamin D intake for all participants was 4·0 (sd 3·3) µg/d and 3·1 (sd 2·3) µg/d for the subgroup. Bland–Altman plots for these intakes showed high agreement. Validity coefficients for the FFQ, 24 h recall and biomarker were ρ QI =0·847 (95 % CI 0·564, 0·928), ρ RI =0·810 (95 % CI 0·537, 0·997) and ρ BI =0·499 (95 % CI 0·190, 0·840), while the correlation coefficients were 0·686, 0·422 and 0·404. Conclusions: The FFQ applied in the present study is a valid tool for assessing dietary vitamin D intake in women living in Serbia, a region without mandatory vitamin D food fortification.